Occurrence of white spot syndrome (WSS) in a prawn farm at Cochin - Jose, Jasmine K; Manissery, Mary K (Indian Journal of Fisheries, 2011)
Occurrence of White Spot Syndrome (WSS) was notiped in farm reared Penaeus indicus H. Milne Edwards of size group 110- 150 mm at Munambam, Cochin in January 1997. The affected prawns showed symptoms, similar to those reported in P. monodon, such as sluggish movements, absence of feeding, escape reactions, reddish discolouration, white spots on cephalothorax and abdomen and loss of part of one or both the antennae. Histopathology of hindgut from the affected P. indicus revealed the presence of inclusion bodies